Les contradictions d’un espace public produit dans la proximité - Antoine Fleury (L'Espace Politique)
The present article provides a critical analysis of urban governance as it is applied to public spaces in inner Paris. For a long time, the centralised city administration was solely interested in technical and functional aspects. Recently however, the local scale has increasingly been considered the more accurate level of public intervention and improving the living environment a primary goal. Hence, new development patterns and modes of public action are being locally implemented (at the quartier level). New actors have emerged in the decision-making process, such as users’ and residents’ associations, as well as the individual residents themselves. These new modes of producing public spaces have yet to be evaluated critically, as they raise a number of issues. Far from contributing to social cohesion, they serve urban marketing strategies that promote a form of governance based on proximity and participation. Local interests now increasingly shape improvement choices and they are mainly the interests of residents. But these interests often contradict other features of the city. This is why it seems necessary to reflect on the scale of public space production.